1985
DOI: 10.1093/oxfordjournals.aje.a114051
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Immunodeficiency Syndrome Among Patients Attending Hemophilia Treatment Centers and Mortality Experience of Hemophiliacs in the United States

Abstract: The acquired immunodeficiency syndrome (AIDS) was first recognized among hemophiliacs in 1982. The authors have conducted investigations to determine the onset and incidence of AIDS among hemophiliacs and to determine trends in hemophilia mortality since the introduction of clotting-factor concentrates in the late 1960s. A survey of United States hemophilia treatment centers, supported by the Centers for Disease Control and the National Hemophilia Foundation, defined a population of hemophiliacs which was moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
1

Year Published

1987
1987
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 0 publications
1
52
0
1
Order By: Relevance
“…In the 1960s and 1970s, the introduction of factor replacement therapy, the development of comprehensive hemophilia treatment centers, and the implementation of home care for this population decreased the number and proportion of deaths due to hemorrhage [7], dramatically increasing their median age at death [33,34]. In this study, these perturbations are underscored by the disparity in the median age at death in 1995-1998 for persons with hemophilia A between those with HIV-related disease (33 years) and those without HIV-related disease (72 years).…”
Section: Continuing Importance Of Hemorrhagic Phenomenamentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1960s and 1970s, the introduction of factor replacement therapy, the development of comprehensive hemophilia treatment centers, and the implementation of home care for this population decreased the number and proportion of deaths due to hemorrhage [7], dramatically increasing their median age at death [33,34]. In this study, these perturbations are underscored by the disparity in the median age at death in 1995-1998 for persons with hemophilia A between those with HIV-related disease (33 years) and those without HIV-related disease (72 years).…”
Section: Continuing Importance Of Hemorrhagic Phenomenamentioning
confidence: 99%
“…By 1982, 73% of persons with hemophilia A treated at U.S. hemophilia treatment centers received lyophilized concentrates, with the majority receiving their therapy almost exclusively at home [7]. Home infusion enabled earlier treatment of hemorrhages and markedly reduced their severity.…”
Section: Introductionmentioning
confidence: 99%
“…Although this flgure was still markedly below that of the general population, he also observed that the death rates for the younger patients in the last 10 years of his study were approaching those of the general Swedish population. Johnson et al (1985) found the age-adjusted mortality among United States haemophiliacs during 1978-82 to be 2-3 times äs high äs that of the general male population. Some deaths may have been missed, however, since this result was based on reported deaths and visits to haemophilia centres, rather than on a cohort study.…”
mentioning
confidence: 94%
“…A pharmacologic consideration for the use of ZDV in hemophilia patients with HIV disease is the presence of chronic hepatitis among many of these patients and the potential for impaired drug metabolism (2,3,6,(8)(9)(10). A recent report on the disposition of a single oral dose of ZDV in patients with hemophilia described considerable variability with regard to the concentrations in plasma attained (12).…”
mentioning
confidence: 99%